Rickettsia rickettsii (Rickettsiales: Rickettsiaceae) Infecting Amblyomma sculptum (Acari: Ixodidae) Ticks and Capybaras in a Brazilian Spotted Fever-Endemic Area of Brazil. Issue 1 (28th August 2019) - Costa, Francisco B; Gerardi, Monize; Binder, Lina de C; Benatti, Hector R; Serpa, Maria Carolina de Azevedo; Lopes, Beatriz; Luz, Hermes R; Ferraz, Katia M P M B; Labruna, Marcelo B
Abstract: The bacterium Rickettsia rickettsii is the agent of Brazilian spotted fever (BSF), a highly fatal disease that is transmitted in Brazil mainly by the tick Amblyomma sculptum Berlese, which uses capybaras ( Hydrochoerus hydrochaeris Linnaeus) as major hosts. In 2015, we captured nine capybaras in a BSF-endemic area of southeastern Brazil. From each capybara, we collected blood sera that were tested through the immunofluorescence assay using Rickettsia spp. antigens, and A. sculptum ticks, processed for isolation of R. rickettsii through guinea pig inoculation. All capybaras (100%) were seroreactive to Rickettsia spp., with highest titers to R. rickettsii . A total of 166 A. sculptum ticks were macerated and inoculated into nine guinea pigs, from which only one presented high fever and seroconverted to R. rickettsii . Blood from this febrile animal was inoculated into additional guinea pigs (guinea pig passages), which also became febrile and seroconverted, or when euthanized during the fever period, their internal organs (spleen, lung) were shown to contain R. rickettsii DNA. The present rickettsial isolate has been maintained cryopreserved as infected guinea pig organs. There was at least one R. rickettsii- infected tick among the 166 macerated ticks, giving a minimal infection rate of 0.6% (1/166). This infection rate is within the range of previous studies, which reported that only 0.05% to at most 1.28% A. sculptum ticks were infected by R. rickettsii in other BSF-endemic areas. These low infection rates support the low incidence of BSF, despite of A. sculptum being the most frequent human-biting tick in southeastern Brazil.